Dampak Sebuah Nikah Bawah Tangan Presfektif Hukum Islam - Sumiati Sumiati; Jamaluddin Jamaluddin (Departement of Mathematics Education, 2023)
This research explains that the main purpose of marriage is to build a lasting and happy household life between husband and wife with the intention of continuing offspring. Given that marriage is an instinctive human demand for offspring for the continuation of life and obtaining peace of life and fostering and cultivating human affection. The harmony that exists between two souls will make them integrated in the world of love and togetherness. Marriage for mankind is something very sacred and has a sacred purpose as well, and is inseparable from religious provisions. People who enter into a marriage are not merely to satisfy the lust that is perched in their souls, but to achieve peace, tranquility and mutual nurturing between husband and wife based on deep love and affection.